STUDYING TAXATION - NECESSITY AND OPPORTUNITY - Carmen, COMANICIU (Strategii Manageriale)
Taxation - a set of laws, regulations and methods of establishing taxes - is, was and will always be present in the life of every individual and every company because of the existence of the State with the tasks and functions, through its influence on the economic and social. Most persons understand the necessity of taxation, but how many people can provide relevant answer to questions such as: What is taxation and which are its characteristics? What is the significance of taxation? What are the tax effects at the micro level? How important is the ratio between direct taxation and indirect taxation? What are the principles of taxation? How are taxes determined? What are the rights and obligations of taxpayers? How taxation can become a stimulating factor? Through this article we will try to emphasize the necessity of studying taxation, in order to be a real partnership between the taxpayer and the state, with appropriate action. Without claiming an exhaustive approach we believe that the aspects presented can be points of reflection for each individual, so that it to be open at any time to study taxation, realizing the importance of skills and abilities that can be acquired.